Educators’ Perspectives on the Impact of COVID-19 on Early Childhood Education Level in Indonesia - Saifuddin Saifuddin; Jazariyah Jazariyah; Novita Pancaningrum (STAI Hubbulwathan Duri, 2022)
Covid-19 pandemic has disrupted education, including early childhood education level. Since then, The Indonesian government has asked educational institutions to apply learning from home. Schools all over the country are closed. Changes in the way to teach and learn certainly have an impact. The study aims to consider the impact of the Covid-19 pandemic on the educational process on early childhood education level in Indonesia based on Educator perspectives. Research data were obtained based on a survey and a semi-structured interview with 61 kindergarten educators. All participants were from Indonesia. Data were collected from April-June 2021. Data analysis used thematic analysis of qualitative data. The result revealed four themes: Educators competency Impact, Effect on parents/family, effect on School Management, and effect on educators’ finances.